Comparing doctors' and nurses' accounts of how they provide emotional care for parents of children with acute lymphoblastic leukaemia. Issue 2 (4th October 2011) - Forsey, Mary; Salmon, Peter; Eden, Tim; Young, Bridget
Abstract Objective Despite the emphasis that communication skills training (CST) programmes place on attending to the emotional care of patients, evidence suggests that practitioners neglect this aspect of patient care. We describe and compare doctors' and nurses' accounts of managing the emotional care of parents of children with leukaemia, with the overall objective of examining how their accounts might inform training and policy. Methods Audio‐recorded qualitative interviews with 30 doctors and nurses working in six UK paediatric oncology and haematology treatment centres were analysed interpretatively, drawing on the constant comparative method. Results Doctors' and nurses' descriptions of managing emotional care differed markedly. Doctors described reassuring parents through their ongoing clinical care of the child and by explaining the potentially curative nature of treatment. Doctors did not think they could reassure parents by eliciting and explicitly discussing parents' fears. In contrast, nurses relied on psychological skills and explicit discussion of parents' emotions to provide reassurance. Both doctors and nurses relied on each other to ensure that parents' emotional needs were met by the multidisciplinary team rather than by individual practitioners. Conclusion Nurses' accounts of providing emotional care resembled the emphasis on explicit emotional talk in CST. However, doctors' accounts indicated that they provided emotional care in ways that diverged markedly from expectations in CST but that were more consistent with their biomedical and authoritative role in patient care. These findings may have implications for CST in future revisions of guidelines, but work is first needed to explore parents' perspectives on emotional care. Copyright © 2011 John Wiley & Sons, Ltd.